Upaya Meningkatkan Kemampuan Membandingkan Pecahan Sederhana Dengan Menggunakan Kartu Pecahan Di Kelas III SD Negeri Majalaya VII - Sugi Alibowo (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2018)
This study aims to improve the mathematics learning outcomes of third grade students of Majalaya VII Elementary School in simple fraction materials using fractional card media. The use of this media is done through a game. This type of research is classroom action research. This study uses the Kemmis and Taggart model. The subjects in this study were third grade students of Majalaya VII State Elementary School, totaling 24 students. The techniques used for data collection are observation and written test techniques. The research instrument uses student observation sheets and written tests. Data analysis techniques used are descriptive quantitative and qualitative descriptive. Based on the results obtained it can be concluded that: the completeness of mathematics learning outcomes using fractional card media in third grade students of Majalaya VII State Elementary School has increased. The increase in the first cycle was 62.50% while in the second cycle was 79.17%.